The Role of Brand Identity in Creating Resilient Small Enterprises (SMEs) in Fashion Industry - Rosita Binti Mohd Tajuddin; Siti Fatimah Binti Hashim; Amer Shakir Binti Zainol (International Journal of Supply Chain Management, 2017)
Small fashion enterprises in Malaysia are not quite familiar with the role of brand identity in creating resilient in business treats. They are categorized as SMEs which consist of almost 90% of businesses in Malaysia. The government of Malaysia has developed many entrepreneurship programs and funds to assist SMEs to be competitive. However, the government acknowledged the lack of experience and exposure among SMEs towards branding has led to difficulties for business sustainability. Thus, this research paper focuses on small enterprises in Malaysia who operate fashion businesses and encounter tough competition in the market, This study examined on how brand identity can create resilient SMEs for sustainability. It is crucial for them to establish brand identity as competitive advantage to their business resilience. A case study of ten (10) small fashion enterprises located in Klang Valley showed that they are in need to employ brand identity towards building a stronger corporate entity in order to be resilient in the market.